The Relative Frequency of Helicobacter Pylori Infection in Proximal and Distal Gastric Carcinomas - Muhammad, Asim; Shah, Walayat; Salam, Abdul; Sajjad, Muhammad (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
Objectives: To find out the relative frequency of H. pylori infection in proximal and distal gastric adenocarcinomas and to determine its relationship with other environmental and familial factors responsible for gastric carcinogenesis. Methodology: This cross sectional study was conducted on Afghani patients with gastric cancer. A total of 72 gastric adenocarcinoma patients, with equal number (36) of proximal and distal gastric cancer, were enrolled from Northwest General Hospital & Research Center and Rehman Medical Institute, Peshawar. After informed written consent multiple gastric biopsies were taken from all the patients and were processed. Sections were stained with H&E and Giemsa for histology and H. pylori detection respectively. Results: The overall frequency of H. pylori was 29.2% (21/72) with no statistically significant difference (p=0.346) between proximal (48.2%) and distal (57.1%) gastric adenocarcinoma. Males were more affected by H. pylori associated cancers. Proximal tumors were more common in the younger age group and distal tumors in the older age group. A higher frequency of tobacco use, intake of high salty diet in combination with a high temperature diet were found to be more related to proximal gastric tumors. No significant difference was observed regarding the main histological types of gastric adenocarcinomas among the proximal and distal gastric tumors and also in their relation to H. pylori infection. Conclusion: H. pylori infection is equally common in the proximal and distal gastric adenocarcinomas in the Afghani patients with gastric cancer especially on the north eastern border near to Pakistan. Proximal gastric tumors are more associated with tobacco use and dietary factors. Key words: Helicobacter pylori, frequency, gastric adenocarcinoma, proximal gastric cancer, distal gastric cancer, dietary factors